TGFβ counteracts LYVE-1-mediated induction of lymphangiogenesis by small hyaluronan oligosaccharides - Bauer, Jochen; Rothley, Melanie; Schmaus, Anja; Quagliata, Luca; Thiele, Wilko; Sleeman, Jonathan P. (Journal of molecular medicine, 2018)
During tissue injury, inflammation, and tumor growth, enhanced production and degradation of the extracellular matrix glycosaminoglycan hyaluronan (HA) can lead to the accumulation of small HA (sHA) oligosaccharides. We have previously reported that accumulation of sHA in colorectal tumors correlates with lymphatic invasion and lymph node metastasis, and therefore, investigated here are the effects of sHA on the lymphatic endothelium. Using cultured primary lymphatic endothelial cells (LECs) and ex vivo and in vivo lymphangiogenesis assays, we found that in contrast to high-molecular-weight HA (HMW-HA), sHA of 4-25 disaccharides in length can promote the proliferation of LECs and lymphangiogenesis in a manner that is dependent on their size and concentration. At pathophysiologically relevant concentrations found in tumor interstitial fluid, sHA is pro-proliferative, acts synergistically with VEGF-C and FGF-2, and stimulates the outgrowth of lymphatic capillaries in ex vivo lymphangiogenesis assays. In vivo, intradermally injected sHA acts together with VEGF-C to increase lymphatic vessel density. Higher concentrations of sHA were found to induce expression of the anti-lymphangiogenic cytokine TGFβ in LECs, which serves to counter-regulate sHA-induced LEC proliferation and lymphangiogenesis. Using appropriate knockout mice and blocking antibodies, we found that the effects of sHA are mediated by the sialylated form of the lymphatic HA receptor LYVE-1, but not by CD44 or TLR-4. These data are consistent with the notion that accumulation of sHA in tumors may contribute to tumor-induced lymphangiogenesis, leading to increased dissemination to regional lymph nodes. Key messages sHA promotes lymphangiogenesis primarily through increased LEC proliferation sHA induces proliferation in a narrow concentration window due to upregulated TGFβ Smaller HA oligosaccharides more potently induce proliferation than larger ones VEGF-C and FGF-2-induced LEC proliferation and lymphangiogenesis is augmented by sHA Sialylated LYVE-1, but not CD44 or TLR-4, mediate the effects of sHA on LEC
First online 27 December 2017
Gesehen am 26.10.2018